Data errors caused by surge voltages on paired-conductor lines. - Chrysanthou, C. (IEEE Transactions on power delivery)
Impulse voltages may be coupled onto paired-conductor telecommunication lines by lightning or by disturbances on nearby power lines. These common-mode impulses are converted to differential-mode by unbalance of the conductors or by operation of surge protectors. Many of these differential-mode impulses can cause large numbers of bit errors and interfere with digital transmission. Statistical models have been previously developed to determine the common-mode to differential-mode conversion of impulse voltages on cable pairs. In this paper, these models are used to predict interference with digital transmission during lightning activity. This possible interference is expressed as expected number of errored seconds within one hour of lightning activity. Since operation of surge protectors causes data errors, this paper also examines how impulse limiting voltage of protectors affects data disturbances